2016
DOI: 10.1007/s00432-016-2265-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival variability of controls and definition of imaging endpoints for longitudinal follow-up of pancreatic ductal adenocarcinoma in rats

Abstract: The early detection by the means of animal imaging of one or more signs indicating the onset of a critical step in the development of the disease (e.g., ascites or/and metastasis) allows the researcher to prevent the occurrence of animal pain, thereby ensuring better animal welfare. However, using a single standard control group in an effort to use fewer animals for a given model runs such a significant risk of false results that it mars the entire study. Although reducing the number of animals in a study rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…More ascites were observed in mice with wild type Panc2 cells, while mice implanted with SLC5A1-knockdowned Panc-2 cells due to the smaller tumor burden and progression (data not shown). A previous study has shown that ascites was a significant factor leading to poor survival of pancreatic cancer animals 44. Although we cannot fully address the reason of better survival in the knockdown group, it is possible that less ascites are associated with better prognosis of mice with SCL5A1-knockdowned Panc-2 cells.…”
Section: Discussionmentioning
confidence: 72%
“…More ascites were observed in mice with wild type Panc2 cells, while mice implanted with SLC5A1-knockdowned Panc-2 cells due to the smaller tumor burden and progression (data not shown). A previous study has shown that ascites was a significant factor leading to poor survival of pancreatic cancer animals 44. Although we cannot fully address the reason of better survival in the knockdown group, it is possible that less ascites are associated with better prognosis of mice with SCL5A1-knockdowned Panc-2 cells.…”
Section: Discussionmentioning
confidence: 72%
“…A total of 384 references were identified by electronic search; 338 full-text studies were evaluated in accordance with the eligibility criteria and 290 were excluded. Finally, 48 studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] complied with all the established eligibility criteria and were included in the study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%